2019
DOI: 10.1210/en.2019-00362
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Patient-Derived Endometrial Cancer Stem-like Cells Generated by Three-Dimensional Culture

Abstract: Low-grade and early-stage endometrial cancer usually has a favorable prognosis, whereas recurrent or metastatic disease is often difficult to cure. Thus, the molecular mechanisms underlying advanced pathophysiology remain to be elucidated. From the perspective of the origin of advanced endometrial cancer, the characterization of cancer stem-like cells (CSCs) will be the first step toward the development of clinical management. We established long-term culturable patient-derived cancer cells (PDCs) from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Another target evaluated in preclinical setting was ALDH1. Inhibition of ALDH activity with disulfiram and N, N Diethylaminobenzaldehyde (DEAB) reduces proliferation of spheroids composed by CSCs [99]. On the other hand, an antibody directed against Epithelial membrane protein-2 (EMP2) (a protein involved in tumor migration and neoangiogenesis) reduces tumor formation and growth in ALDH1 + cells and indirectly downregulates ALDH1 expression although the precise mechanism of action is not clear [100].…”
Section: Agents Targeting Cscs In Ec: Preclinical Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Another target evaluated in preclinical setting was ALDH1. Inhibition of ALDH activity with disulfiram and N, N Diethylaminobenzaldehyde (DEAB) reduces proliferation of spheroids composed by CSCs [99]. On the other hand, an antibody directed against Epithelial membrane protein-2 (EMP2) (a protein involved in tumor migration and neoangiogenesis) reduces tumor formation and growth in ALDH1 + cells and indirectly downregulates ALDH1 expression although the precise mechanism of action is not clear [100].…”
Section: Agents Targeting Cscs In Ec: Preclinical Developmentmentioning
confidence: 99%
“…Being known that estrogens stimulate growth of ER + CSC spheroids with upregulation of IL6, IL1B an IL18 [99], Guy and colleagues showed that MPA decrease CD133 + populations both in ER + /PgR + but also in ER − /PgR − cell lines. Moreover there was a reduction in CD133 + cells in samples of patients who responded to MPA treatment although number of samples was small (only 4 patients) and they all showed ER positivity [113].…”
Section: Agents Targeting Cscs In Ec: Preclinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, lncRNA studies using ovarian tumor specimens or other ovarian cancer models are strongly demanded. Three-dimensional cultures of patient-derived cancer cells (PDCs) and cancer models established by transplanting tumor specimens into host mice (patient-derived xenograft [PDX] models) retain the properties of original tumors and have attracted attention as promising models for cancer research and drug screening ( Ishiguro et al, 2016 ; Maru and Hippo, 2019 ; Namekawa et al, 2019 ; Shiba et al, 2019 ). Further studies using PDC and PDX models would advance the application of apoptosis-related lncRNAs to ovarian cancer diagnosis, prognosis, and therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In chemoresistant OC cell lines, DEAB treatment significantly inhibited P-glycoprotein (P-gp) protein and breast cancer resistance protein (BRCP) transcript and protein, re-sensitizing the cell lines to chemotherapy [82]. Similarly, DEAB effectively inhibited the proliferation of spheroids generated from patient-derived endometrial CSCs [104] (Table 2). However, it is also important to note that the selectivity of DEAB for different ALDH isoforms is low.…”
Section: -Diethylaminobenzaldehydementioning
confidence: 97%